Psychoeducational Learning Enhancement through Extracurricular Theatre Rehearsal: Case Study of EFL Students at the Higher School of Teachers (ENS Assia Djebar Constantine) - Madoui, Khalida (Milev Journal of Research and Studies, 2022)
This article tackles the psychoeducational learning milieu where the researcher, lecturer of literature, dealt with challenges EFL students are facing in class and how through extra-curricular activities she could manage to incite them on a theater stage and break the ice between them and literature. The aim of the article is to discuss the difficulties of EFL students in grasping literature lectures and to present an attempt from the part of the researcher as a lecturer to improve the students’ learning process and performances through theatre rehearsal. The paper describes mainly an experience with my students from the ENSC Assia Djebar and demonstrate the psychological effects as art on stage tantalized their inner child and enhanced notably their educational performance. The descriptive analysis of these effects is based on two questionnaires that unveil how the inner child was emerging through rehearsals and how art was helping students transcend their fears and shyness. Observation also served deeply to witness the progress of the students as art on stage cured their inner child after its disinhibition. The outcome of the theatrical experience shows that theatre is a real ice breaker in classes as it copes with the inner child of students that cherished role plays when young. Art heals the inner child of the students and this enhances educational performance in class.